An examination of DMO network identity using Exponential Random Graph Models. (October 2018) - Williams, Nigel L.; Hristov, Dean
Highlights: Inferential network analysis can identify the extent to which network identity was established in a DMO member initiative. Firms exhibited homophily by industry only, suggesting that a distinct network identity was not yet established. Inferential network analysis can validate insights from descriptive analysis. DMOs need to engage in deliberate hub development strategies, to establish a destination network identity.